Syariah Obligation: Prospects and its Challenges in Indonesia - Sudirman Sudirman; Bakri Bakri (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This writing is designed to investigate prospects and challenges facing Syariah Obligation (sukuk) in Indonesia. In this study, we found Syariah obligation (sukuk) development have good prospect. There are factors supporting Syariah obligation (sukuk) in Indonesia, some of which are significant population, government support, and domestic economic stability over percent per year, flow of fresh fund by Middle East, and making complete regulatory framework, as well as the rise of global Syariah market. Notwithstanding sukuk potential, some challenges are exist, for examples, drawback of regulation, uncertainty of taxation, most of Syariah financial products are â€œdebt-basedâ€ or â€œdebt-likelyâ€, less investor understanding of Syariah obligation instrument, and not quite conducive investment climate and complicated bureaucracy.